The Foreign Direct Investments in Nepal - Sporek, Tadeusz (Bezpośrednie inwestycje zagraniczne w Nepalu, 2010)
Nepal does not attract much foreign direct investment in spite of policy reforms initiated in the early 1990s to attract it. This is partly because a small, poorly developed, landlocked, mountainous country has little to offer to investors. Although FDI and Technology Transfer Act liberalized the entry of FDI and guaranteed repatriation of profit and capital, investors still face obstacles. The challenge for Nepal is to create an investors-friendly business climate that will complement its small bureaucracy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 294-305
Keywords: Foreing Direct Investment; Nepal; technology transfer; financial sector